Optimizing the resistance spot-welding process for dissimilar stainless steels - T Khuenkaew; K Kanlayasiri (My University, 2018)
The objective of this study was to identify the ideal welding circumstances to conduct resistance spot-welding in the case of 316 austenite and 425 ferrite stainless steels, which offer the challenge of being dissimilar. The study examines a number of welding variables, including weld current, weld time, hold time, electrode force, and the upper and lower electrode types. Initially, a 26-1 fractional factorial design was used for the screening of variables involved in the process. After this stage, the Box-Behnken design was employed for analysis of those variables and in order to specify the multiple response optimizations applicable to the size of nuggets through examination of the desirability function. The experiment was run using a resistance spot-welding machine at 50 kVA, 50 Hz. The quality of welded specimens was determined by their penetration, nugget diameter and nugget area. The optimal welding conditions were found to be 3.3 kN of electrode force, 25 cycles of weld time, 10,000 amperes of weld current, 50 cycles of hold time, and both R30 types of up-low electrodes. The optimal welding conditions provided nugget sizes of quality which were able to pass the specifications of the customer.
Keywords: Spot welding; Fractional factorial design; Advanced Welding Techniques Analysis